Pemanfaatan Digital Marketing Sebagai Aktivitas Promosi dan Pemasaran Di SMKS Muhammadiyah 3 Cerme - Putra Panji Respati; Nur cahyadi; Alif Sulthon Basyari; Aries Kurniawan (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
The development of information technology is one of the tools that can be used to convey information and exchange data. The world of education really needs a solution in promoting it according to the school's targets and goals. An effective and efficient education marketing strategy will have a very good feedback impact on schools because the school's image is easily recognized by students. One form of utilizing information technology that can be used is the maximum utilization of social media such as Facebook, Instagram, WhatsApp and also TikTok. This media is often used by consumers, especially students, to be able to find information according to their wishes. Conventional marketing can also be applied on an ongoing basis, such as brochures, banners, billboards, etc. to maintain direct social interaction. The use of social media as a promotional platform is expected to be able to solve problems faced by partners in the world of education and meet needs according to the desired target, supported by competent human resources and facilities to support ongoing activities. The implementation of mentoring activities for partners is carried out using the Focus Group Discussion (FGD) method in order to be able to establish openness, trust and understand perceptions, attitudes and experiences of problems faced by partners in carrying out promotions, which is then followed by direct assistance and training in the use of social media applications.